Optimalisasi Blog Sebagai Media Promosi Digital Pada UMKM Bakso Brakbruk Khas Purwokerto di Kota Padang - Syinta Yollivia; Riani Hutajulu; Novadilastri Novadilastri; Sularno Sularno (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2025)
Digital technology development provides significant opportunities for MSMEs to enhance competitiveness through online marketing. Bakso Brakbruk MSMEs typical of Purwokerto in Padang City face challenges in utilizing digital media to expand market reach. Blogs as digital platforms have the potential to increase product visibility and build communication with consumers. This community service aims to analyze the use of blogs as a digital marketing strategy for Bakso Brakbruk MSMEs. The method used is a qualitative descriptive approach through observation, interviews, and documentation to collect data on blog implementation in marketing activities. Results show that blog usage can increase brand awareness, facilitate customer interaction, and present comprehensive product information. Optimal blog implementation requires consistent content strategies and understanding of local target market characteristics. Blog usage proves effective as an economical promotional medium for developing traditional culinary businesses in the digital era.